Remifentanil protects the ovaries against ischaemia-reperfusion injury in rats - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2016)
Ovarian ischaemia reperfusion (I/R) injury may affect fertility. Protecting ovaries against organ damage is therefore clinically important. In this study, we assessed the effects of remifentanil and investigated whether it has a protective effect. Eighteen female Wistar albino rats were assigned to three groups (n = 6): a sham group, an ischaemia reperfusion (I/R) group, and an ischaemia reperfusion and remifentanil (I/R+R) group. Rats exposed to experimentally induced I/R injury. Two-hour periods of ischaemia were followed by 1 h of reperfusion in the I/R and I/R+R groups. After ischaemia, no drug was administered in the sham and I/R groups. In the I/R+R group, remifentanil infusion (2 mu g/kg/min) was started in the last 30 min of the ischaemia period, and continued until the end of reperfusion. After the ischaemic and reperfusion period, the ischaemic ovaries were surgically removed for biochemical and histopathologic examination. Tissue damage scores (dense vascular congestion, oedema, and loss of cohesion) were examined. Malondialdehyde levels and catalase enzyme activity in tissue were measured. We found significantly lower tissue damage scores in the I/R+R group than in the I/R group (P < 0.05). The administration of remifentanil significantly decreased oxidative stress (malondialdehyde level) (P < 0.05), and significantly increased antioxidant enzyme (catalase enzyme) activity compared with the ischaemia reperfusion group (P < 0.05). These findings suggest that remifentanil has a protective effect against ovarian ischaemia reperfusion injury and can be used safely in ovarian torsion surgery.
Keywords: Remifentanil; ovary; ischaemia; enzymes; rat; CEREBRAL-ISCHEMIA; ISCHEMIA/REPERFUSION INJURY; LIPID-PEROXIDATION; ADNEXAL TORSION; DETORSION; TIME